Loss of Interleukin-6 Influences Transcriptional Immune Signatures and Alters Bacterial Colonization in the Skin - Luckett-Chastain, Lerin R.; King, Catherine J.; McShan, William M.; Gipson, Jenny R.; Gillaspy, Allison F.; Gallucci, Randle M. (Frontiers in Microbiology, 2021)
Skin functions as a protective barrier to inhibit the entry of foreign pathogens, all the while hosting a diverse milieu of microorganisms. Over time, skin cells, immune cells, cytokines, and microbes interact to integrate the processes of maintaining the skins’ physical and immune barrier. In the present study, the basal expression of two immunologically divergent mouse strains C57BL/6, BALB/c, as well as a strain on the C57 background lacking IL-6, was characterized. Additionally, cutaneous antimicrobial gene expression profiles and skin bacterial microbiome was assessed between strains. Total RNA sequencing was performed on untreated C57BL/6 (control), BALB/c, and IL-6 deficient skin samples and found over 3400 genes differentially modulated between strains. It was found each strain modulated its own transcriptional “profile” associated with skin homeostasis and also influenced the overall bacterial colonization as indicated by the differential phyla present on each strain. Together, this data not only provides a comprehensive view of the transcriptional changes in homeostatic skin of different mouse strains; but also highlights the possible influence of the strain differences (eg. Th1/Th2 balance) as well as a role for IL-6 in overall skin immunity and resident microbial populations.